1993
DOI: 10.1172/jci116605
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively modified low density lipoprotein is a chemoattractant for human T lymphocytes.

Abstract: Oxidatively modified low density lipoprotein (Ox-LDL) is a known chemoattractant for monocytes. Here we demonstrate, using a modified Boyden chamber assay, that human peripheral blood T lymphocytes, but not B lymphocytes, also respond chemotactically to Ox-LDL, showing a threefold increase over control and an optimum response at 10 ;tg/ml. Copper and endothelial cell-oxidized LDL and #l-VLDL were used and gave similar results. The activity was not chemokinetic and native LDL possessed no chemoattractant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
0
11

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(127 citation statements)
references
References 30 publications
3
113
0
11
Order By: Relevance
“…Moreover, it is well known that OxLDL induces a variety of cellular responses in vascular wall cells and circulating cells. For example, OxLDL is a chemoattractant for endothelial cells and T-lymphocytes (39,40). It increases the expression of VCAM-1 and P-selectin and the release of endothelin and interleukin-8 (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is well known that OxLDL induces a variety of cellular responses in vascular wall cells and circulating cells. For example, OxLDL is a chemoattractant for endothelial cells and T-lymphocytes (39,40). It increases the expression of VCAM-1 and P-selectin and the release of endothelin and interleukin-8 (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, LPC has been shown to be chemotactic for T lymphocytes and monocytes. 33,34 An interesting possibility is that antibodies to LPC/oxLDL could form immune complexes, which could be taken up by phagocytosis in the artery wall, leading to foam cell formation. In line with this, PLA 2 -modified LDL is taken up by macrophages, which develop into foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…6), although it is widely unknown where, how, and to what extent oxidized LDL (oxLDL) is generated during atherogenesis. It was shown that oxLDL is involved in recruitment of monocytes and lymphocytes (113,134); for example, via stimulating endothelial cells and smooth muscle cells to secrete monocyte chemotactic protein-1 (MCP-1) (Fig. 6) (120,136).…”
Section: Protein Oxidation In Other Age-related Diseasesmentioning
confidence: 99%